2022
DOI: 10.1016/j.isci.2021.103619
|View full text |Cite
|
Sign up to set email alerts
|

The short neuropeptide F regulates appetitive but not aversive responsiveness in a social insect

Abstract: The neuropeptide F (NPF) and its short version (sNPF) mediate food-and stressrelated responses in solitary insects. In the honeybee, a social insect where food collection and defensive responses are socially regulated, only sNPF has an identified receptor. Here we increased artificially sNPF levels in honeybee foragers and studied the consequences of this manipulation in various forms of appetitive and aversive responsiveness. Increasing sNPF in partially fed bees turned them into the equivalent of starved ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 94 publications
(135 reference statements)
1
14
0
Order By: Relevance
“…Whereas the two control groups (sham and DMF) showed similarly low responsiveness scores (mean rank comparison, not significant), the highest dose of both dopamine and 6,7-ADTN significantly increased sucrose scores ( P < 0.0001). We confirmed this finding in bees availing themselves of an even higher energy supplement as they were individually fed with a mixture of honey, pollen, and sucrose solution ( 24 26 ) before the sucrose-responsiveness assay. Enhancing dopamine levels in these bees rescued their appetitive responsiveness (fig.…”
supporting
confidence: 70%
“…Whereas the two control groups (sham and DMF) showed similarly low responsiveness scores (mean rank comparison, not significant), the highest dose of both dopamine and 6,7-ADTN significantly increased sucrose scores ( P < 0.0001). We confirmed this finding in bees availing themselves of an even higher energy supplement as they were individually fed with a mixture of honey, pollen, and sucrose solution ( 24 26 ) before the sucrose-responsiveness assay. Enhancing dopamine levels in these bees rescued their appetitive responsiveness (fig.…”
supporting
confidence: 70%
“…Note that this procedure has an intrinsic variability that depends on the amount of Fura-2 delivered by the experimenter and on the number of labeled projection neurons. Still, multiple studies have shown convergent results on odor-elicited glomerular responses, indicating that such a procedure remains valid to investigate olfactory processing in the honey bee antennal lobe (Hourcade et al, 2009; Locatelli et al, 2013; Paoli et al, 2016a; Bestea et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Still, multiple studies have shown convergent results on odor-elicited glomerular responses, indicating that such a procedure remains valid to investigate olfactory processing in the honey bee antennal lobe (Hourcade et al, 2009;Locatelli et al, 2013;Paoli et al, 2016a;Bestea et al, 2022).…”
Section: Bee Preparationmentioning
confidence: 99%
“…bumble bees were kept for an hour under these conditions. For each individual, we measured its consumption (μL) of sucrose solution, quinine or distilled water at the end of this period (Desmedt et al, 2016;Bestea et al, 2022).…”
Section: Experiments 1: Appetitive and Aversive Reinforcement Responsesmentioning
confidence: 99%